Competition in Indian Sky, Fly High or Nose Dive... - PJ, Shyju (Atna Journal of Tourism Studies, 2006)
Indian aviation is experiencing a tremendous change in the recent years. Opening of Indian sky for private players made a paradigm shift in domestic air travel. After 1992 the role of Indian Airlines,